Enhancing Speaking Skills Through Code-mixing and Code-Switching in Madurese Context - Achmad Syarofi Al-furqon; Jaftiyatur Rohaniyah; Beny Hamdani (Sustainable, 2025)
Teaching English to students who don't get much exposure to English as a foreign language and still mostly speak their native language, such as Madurese, presents some difficulties and challenges. This study investigates the effectiveness of a teacher's intentional code-mixing and code-switching strategies in an English as a Foreign Language (EFL) on Madurese. Using quantitative research with the pre-experimental design (one group pretest and posttest), the research was conducted in the first semester of the Faculty of Sharia and Economic Islami of Universitas Annuqayah Guluk-Guluk Sumenep. Data were collected from score pre-and post-tests of the students through speaking proficiency. From a one-sample t-test, it showed that there is a significant mean difference between pre-test and post-test in speaking proficiency, and the students' speaking scores are statistically significantly different after the intervention. This finding suggests that the intervention of code-mixing and code-switching by the teacher had a significant positive effect on the students' speaking skills, indicating a large effect as calculated by Cohen's d. The strategic use of code-mixing and code-switching is a powerful pedagogical tool that provides both cognitive scaffolding and affective support. The improvement happens by adopting a nuanced teaching approach that leverages students' native language as a valuable resource to overcome linguistic and psychological barriers in EFL learning.